Variasi Dialek Bahasa Lamaholot di Pulau Adonara, Kabupaten Flores Timur : Sebuah Kajian Sinkronik - Oktofianus Luli Boli; Ramly Ramly; Usman Usman (Indonesian Journal of Social and Educational Studies, 2021)
Abstract. This study aims to describe the phonological variations found in the Lamaholot dialect on Adonara Island, East Flores Regency. The research method used in this research is descriptive qualitative method. As for managing the data, the method used is the proficient method using the face met technique and the listening method with the free, active, proficient listening technique, the note-taking technique and the recording technique. In this study it was found that the language used by the people of Adonara Island at four points of the village was the observation area for phonological variations. Of the 211 questionnaires in the form of vocabulary used by the researcher, the classification became 32 vocabularies that experienced phonological variations. The findings of this language variation are divided into categories of changes in vowel phonemes, changes in consonant phonemes, changes in vowel and consonant phonemes, adding phonemes and deleting phonemes. It is known that the linguistic situation in the observation area is caused by the different geographical conditions and cultural backgrounds between each observation area. Lamahala Jaya Village and Kwaelaga-Lamawato Village, which are located in the East Adonara District, are adrift on the coastal and mountainous locations. The same thing also works in Nisakarang Village and Pepakgeka Village, which are located in Kelubagolit District. Keywords: Language Variation, Phonology Variation, Dialectology, Lamaholot Language